Manufacturing method of crystalline tobermorite-containing hardened body

The autoclave curing method for producing cured bodies with high crystalline tobermorite content addresses the challenge of utilizing fly ash by pre-mixing a strong alkali stimulant with fly ash and cement, resulting in enhanced tobermorite synthesis and effective fly ash utilization.

JP2025054029APending Publication Date: 2025-04-07KMEW CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023163203
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing methods for producing cured bodies with high tobermorite content face challenges in effectively utilizing fly ash, as increasing the amount of fly ash mixed in reduces the tobermorite content.

Method used

An autoclave curing method is employed using a kneading material that includes a silica raw material pre-mixed with a strong alkali stimulant and cement, which enhances the synthesis of crystalline tobermorite, allowing for a higher fly ash content while maintaining a high tobermorite content.

Benefits of technology

This method effectively increases the crystalline tobermorite content in the cured product, enabling the effective utilization of fly ash, which is abundant in industrial waste, thereby promoting sustainable use of industrial by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054029000001
    Figure 2025054029000001
  • Figure 2025054029000002
    Figure 2025054029000002
  • Figure 2025054029000003
    Figure 2025054029000003
Patent Text Reader

Abstract

To provide a method capable of manufacturing a hardened body much containing crystalline tobermorite by effectively using fly ash.SOLUTION: A manufacturing method of crystalline tobermorite-containing hardened body includes performing autoclave curing to a kneaded material including cement and a siliceous material containing fly ash that has been mixed in advance with a strong alkali stimulant.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a hardened body, and more specifically, to a method for producing a hardened body having an increased content of crystalline tobermorite. [Background technology]

[0002] Known conventional techniques for producing hardened bodies include a vacuum degassing step of vacuum degassing a cement-containing material and an extrusion step of extruding the vacuum degassed material, such as the production method disclosed in Patent Document 1. This production method specifically includes a kneading step of adding water to a cement-containing mixed material and kneading it to obtain a material, a vacuum degassing step of vacuum degassing the cement-containing material, an extrusion molding step of extruding the vacuum degassed material to obtain a molded body, and a hardening step of hardening the molded body to obtain a hardened body.

[0003] The material used in this manufacturing method contains cement and, as necessary, contains siliceous materials, reinforcing fibers, aggregates, fillers, thickeners, dispersants, and other materials. By adding water to such a cement-containing material and kneading it, a liquid or highly viscous, fluid kneaded material that is a hydraulic material is obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-126957 A Summary of the Invention [Problem to be solved by the invention]

[0005] The hardened body obtained by the manufacturing technology of Patent Document 1 contains fly ash. From the viewpoint of promoting the use of industrial by-products and limiting disposal sites, it is desired to actively increase the proportion of effective use of fly ash, which is discharged in large quantities from thermal power plants and the like. By replacing part of the siliceous raw material with fly ash, it is possible to effectively use the fly ash, but if a large amount of fly ash is mixed, the tobermorite content of the obtained hardened body decreases.

[0006] Therefore, an object of the present invention is to provide a method for producing a hardened body containing a large amount of crystalline tobermorite by effectively utilizing fly ash. [Means for solving the problem]

[0007] In the method for producing a crystalline tobermorite-containing hardened body according to the present invention, a kneaded material containing cement and a siliceous raw material including fly ash premixed with a strong alkaline irritant is subjected to autoclave curing.

[0008] The ratio of the strong alkaline irritant is preferably 0.05 mass % or more and 1.40 mass % or less with respect to 100 mass % of the fly ash with which the strong alkaline irritant is premixed.

[0009] The ratio of the fly ash pre-mixed with the strong alkaline irritant is preferably 99% by mass or less relative to 100% by mass of the siliceous raw material.

[0010] It is preferable that the siliceous raw material includes a crystalline silica raw material, fly ash pre-mixed with the strong alkaline stimulant, and fly ash not pre-mixed with the strong alkaline stimulant, and the proportion of the crystalline silica raw material is 3 mass% or more relative to 100 mass% of the siliceous raw material, and the proportion of the fly ash pre-mixed with the strong alkaline stimulant is less than 50 mass% relative to 100 mass% of the siliceous raw material.

[0011] It is preferable that the strong alkaline irritant contains potassium hydroxide, and the proportion of potassium hydroxide in the strong alkaline irritant is 90 mass % or more. Effect of the Invention

[0012] According to the present invention, a hardened body containing a large amount of crystalline tobermorite can be obtained. Since the hardened body contains a large amount of fly ash, the fly ash discharged in large amounts from thermal power plants and the like can be effectively utilized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, a method for producing a crystalline tobermorite-containing hardened material (hereinafter also referred to as a high-tobermorite-content hardened material) according to an embodiment of the present invention (hereinafter also referred to as the present embodiment) will be described.

[0014] In order to achieve the above-mentioned object, the inventors of the present invention have conducted various research and experiments, and as a result, have discovered that by mixing a cement-containing material with fly ash pre-mixed with a strong alkaline irritant instead of a portion of the silica powder and other siliceous materials, and then subjecting the mixture to steam autoclave curing at a temperature of 160°C or higher and high pressure, almost the entire amount of the fly ash mixed in large quantities functions as a silica (SiO2) source and reacts with the calcium hydroxide in the cement, resulting in the synthesis of a large amount of crystalline tobermorite, a calcium-silica hydrate compound.

[0015] The method for producing a crystalline tobermorite-containing hardened body of the present invention is based on such findings, and involves subjecting a kneaded material containing cement and a siliceous raw material containing fly ash premixed with a strong alkaline stimulant to autoclave curing. In this method, specifically, for example, cement and a siliceous raw material are mixed, and fly ash premixed with a strong alkaline stimulant is mixed as the siliceous raw material, and reinforcing fibers, lightweight aggregates, bulking materials, etc. are mixed as necessary to obtain a kneaded material, and water is further mixed, and the mixture is subjected to steam autoclave curing at a curing temperature of 160°C or higher.

[0016] "Crystalline tobermorite" is a calcium-silica hydrate compound that has moderate strength and does not change when heated. Therefore, the obtained tobermorite-rich hardened material has improved heat resistance.

[0017] <Method of manufacturing a hardened body with high tobermorite content> In the method for producing a tobermorite-rich hardened body of the present embodiment, a kneaded material containing cement and a siliceous raw material including fly ash premixed with a strong alkaline irritant is subjected to autoclave curing.

[0018] [Mixing materials] The mixing material includes cement and a siliceous raw material containing fly ash premixed with a strong alkaline stimulant. That is, the mixing material includes a cement component and a siliceous raw material, and includes fly ash premixed with a strong alkaline stimulant as the siliceous raw material. "Fly ash premixed with a strong alkaline stimulant" refers to a material obtained by premixing fly ash with a strong alkaline stimulant, and the mixing material is obtained by mixing it with cement, silica powder, fly ash not mixed with a strong alkaline stimulant, and other siliceous raw materials. The mixing material may include other components other than the above components.

[0019] [Cement components] Examples of the cement component include portland cement, fly ash cement, blast furnace cement, alumina cement, high-brain cement, and silica fume cement. These may be used alone or in combination of two or more. Examples of portland cement include ordinary portland cement, high-early-strength portland cement, moderate-heat portland cement, and low-heat portland cement. The blending ratio of the cement component is preferably 15% by mass or more and 70% by mass or less, more preferably 25% by mass or more and 60% by mass or less, based on 100% by mass of the mixed material.

[0020] [Siliceous raw materials] The siliceous raw material plays a role in generating tobermorite by hydrothermal reaction during autoclave curing. As the siliceous raw material, silica powder, fly ash, silica fume, diatomaceous earth, siliceous clay, bentonite, etc. can be used. These may be used alone or in combination of two or more. Among them, it is preferable to use silica powder and fly ash in order to generate more tobermorite. The blending ratio of the siliceous raw material is preferably 5% by mass or more and 80% by mass or less, more preferably 15% by mass or more and 70% by mass or less, based on 100% by mass of the kneaded material.

[0021] In the present invention, it has been found that a crystalline tobermorite-rich hardened body can be produced by using fly ash premixed with a strong alkaline stimulant as the siliceous raw material. That is, in the present invention, it is important that the siliceous raw material contains fly ash premixed with a strong alkaline stimulant (hereinafter also referred to as strong alkaline stimulant pretreated fly ash). In the kneading material used in the manufacturing method for a tobermorite-rich hardened body of this embodiment, the siliceous raw material contains strong alkaline stimulant pretreated fly ash, and in addition to this, it contains, as necessary, for example, fly ash not premixed with a strong alkaline stimulant (hereinafter also referred to as strong alkaline stimulant untreated fly ash), silica powder, silica fume, diatomaceous earth, siliceous clay, bentonite, etc.

[0022] The mass ratio of fly ash contained in the siliceous raw material (hereinafter also referred to as fly ash replacement rate) is preferably large. The larger this value is, the more effective use of fly ash is promoted in the manufacturing method of this embodiment. Specifically, the fly ash replacement rate is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 85 mass% or more, and particularly preferably 90 mass% or more. The fly ash replacement rate can be calculated by the formula (mass of fly ash pretreated with strong alkaline stimulant + mass of fly ash not treated with strong alkaline stimulant) × 100 / (mass of the entire siliceous raw material) (mass%).

[0023] (Strong alkaline stimulant) The term "strong alkaline accelerating agent" refers to a reaction accelerator containing an alkaline metal compound that dissolves Si and Al contained in the kneading material and accelerates the reaction.

[0024] Examples of the strong alkaline stimulant include hydroxides of metal elements, carbonates, silicates, carboxylates, phosphates, etc. Among these, the strong alkaline stimulant preferably contains hydroxides of metal elements.

[0025] Examples of hydroxides of metal elements include Alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide; Alkaline earth metal hydroxides such as magnesium hydroxide, calcium hydroxide, strontium hydroxide, and barium hydroxide; Examples include hydroxides of Group 13 elements such as aluminum hydroxide and gallium hydroxide.

[0026] The strong alkaline stimulant preferably contains hydroxides of alkali metals, alkaline earth metals and Group 13 elements, more preferably contains hydroxides of alkali metals and Group 13 elements, further preferably contains potassium hydroxide, sodium hydroxide and aluminum hydroxide, and particularly preferably contains potassium hydroxide. When the strong alkaline stimulant contains potassium hydroxide, it shows more fly ash solubility and promotes more Si dissolution, and as a result, more crystalline tobermorite can be obtained.

[0027] The strong alkaline irritant used may be in its original form or in a diluted form, so long as it contains an active ingredient for fly ash.

[0028] (Preparation method of fly ash pretreated with strong alkaline irritant) The strong alkaline irritant pre-treated fly ash can be prepared by mixing fly ash with a strong alkaline irritant.

[0029] In this case, it is preferable to allow the strong alkaline stimulant and the fly ash to stand after pre-mixing, thereby providing a time period (hereinafter also referred to as "standing time") for promoting the effect of the strong alkaline stimulant. Here, "standing" means that the strong alkaline stimulant is not brought into contact with cement, and during the standing time, the strong alkaline stimulant acts on the fly ash surface, and the desired Si elution effect can be obtained more. In addition, "standing" does not necessarily mean that no external force is applied, but it is sufficient that no external force is applied that removes the strong alkaline stimulant attached to the surface of the fly ash. This standing time is preferably 5 minutes or more, more preferably 8 minutes or more, and even more preferably 10 minutes or more. The upper limit of the standing time is, for example, 60 minutes or less.

[0030] The proportion of the strong alkaline stimulant is preferably 0.05% by mass or more and 1.40% by mass or less with respect to 100% by mass of the strong alkaline stimulant pre-treated fly ash. If the proportion of the strong alkaline stimulant is less than the lower limit, the amount of crystalline tobermorite produced may be less than when only silica powder is used. If the proportion of the strong alkaline stimulant exceeds the upper limit, the setting speed of the cement may become too high, the moldability of the kneaded material may decrease, and a vacuum deaerated extrusion molded product may not be obtained. The proportion of the strong alkaline stimulant is more preferably 0.20% by mass or more and 1.40% by mass or less, and even more preferably 0.60% by mass or more and 1.20% by mass or less.

[0031] The proportion of the strong alkaline irritant pre-treated fly ash is preferably 99% by mass or less relative to 100% by mass of the siliceous raw material. In this case, the amount of crystalline tobermorite produced can be increased. This proportion is more preferably 70% by mass or less, even more preferably 60% by mass or less, and particularly preferably 50% by mass or less. This proportion is, for example, 10% by mass or more, and preferably 40% by mass or more.

[0032] When the siliceous raw material contains fly ash that has not been treated with a strong alkaline stimulant, it is preferable that the proportion of crystalline silica raw material such as silica powder is 3 mass% or more relative to 100 mass% of the siliceous raw material, and that the proportion of fly ash pre-treated with a strong alkaline stimulant is less than 50 mass% relative to 100 mass% of the siliceous raw material.

[0033] When the strong alkaline stimulant contains potassium hydroxide, the ratio of potassium hydroxide in the strong alkaline stimulant is preferably 90% by mass or more. In this case, crystalline tobermorite is more easily produced, and the amount of crystalline tobermorite produced can be increased. This ratio is more preferably 95% by mass or more, and even more preferably 98% by mass. This ratio may be 100% by mass.

[0034] [Other materials] The kneading material may contain, for example, reinforcing fibers, lightweight aggregates, aggregates containing extenders, etc. Examples of reinforcing fibers include natural fibers such as pulp fibers; organic fibers such as vinylon fibers, polyester fibers, polyamide fibers, acrylic fibers, acetate fibers, polyethylene fibers, and polypropylene fibers; glass fibers; carbon fibers; ceramic fibers; and metal fibers. Examples of lightweight aggregates include inorganic lightweight aggregates such as shirasu balloons, glass balloons, perlite, burned vermiculite, and fly ash balloons; and organic lightweight aggregates such as synthetic resin beads and synthetic resin foams. Examples of extenders include pulverized inorganic boards. The kneading material may contain other materials such as thickeners, dispersants, pigments, and colorants.

[0035] These materials are mixed, water is added, and the mixture is kneaded to obtain a kneaded material.

[0036] [Autoclave curing] The kneaded material thus obtained is subjected to autoclave curing to obtain a crystalline tobermorite-containing hardened body.

[0037] When the kneaded material is subjected to autoclave curing, it is usually molded into a desired shape using a mold or the like to form a molded body (solidified body). In this molding, it is preferable to subject the kneaded material to a vacuum degassing treatment, and this molding is preferably performed by extrusion molding. These can be performed using, for example, a vacuum extrusion molding machine.

[0038] The kneaded material may be subjected to primary curing (hardening curing before autoclave curing) before autoclave curing (secondary curing). The primary curing may be appropriately adjusted depending on the composition of the kneaded material, and examples of the primary curing include room temperature curing and steam curing. The primary curing is performed, for example, at normal pressure, at a temperature of 40°C to 90°C, for a period of 4 hours to 12 hours.

[0039] By subjecting the kneaded material to autoclave curing, a hardened body with a high content of crystalline tobermorite can be obtained. Specifically, after hardening curing before autoclave curing, the molded body is removed from the mold, and steam autoclave curing (high-temperature, high-pressure steam curing) is performed in a known or new steam autoclave device, for example, under saturated steam at a pressure of 10 atm to 30 atm. By subjecting the material to steam autoclave treatment, crystalline tobermorite that cannot be obtained at normal temperature and pressure can be produced.

[0040] The curing temperature in the steam autoclave is preferably a high temperature of 160° C. or more. The curing temperature is more preferably in the range of 160° C. to 200° C. It has been confirmed that when the curing temperature in the steam autoclave exceeds 210° C., the amount of tobermorite produced decreases in some cases.

[0041] In order to produce a sufficient amount of crystalline tobermorite, the curing time in the steam autoclave is desirably 4 hours or more when the curing temperature is about 160° C. From the viewpoint of increasing the amount of crystalline tobermorite produced, a longer curing time is basically advantageous, but taking into consideration the burden on the steam autoclave apparatus operating under high temperature and pressure, it is preferable to set the curing time to, for example, about 5 hours or more and 12 hours or less.

[0042] After the autoclave curing, dry curing may be performed by leaving the high tobermorite content hardened body obtained by the autoclave curing in air at room temperature.

[0043] In the production method of the present invention, it is preferable to carry out both hardening curing before autoclave curing and dry curing after autoclave curing, or to carry out only hardening curing before autoclave curing.

[0044] The tobermorite-rich hardened body obtained by the production method of the present invention contains a large amount of fly ash, and therefore allows for effective use of fly ash discharged in large amounts from thermal power plants and the like. EXAMPLES

[0045] The present invention will be specifically described below with reference to examples, but the present invention is not limited to only these examples.

[0046] <Preparation of fly ash pretreated with strong alkaline irritant> A strong alkaline irritant pre-treated fly ash was prepared for use in the manufacture of a hardened body with a high content of crystalline tobermorite. As shown in the "Strong alkaline irritant selection experiment" below, this preparation was carried out by changing the type of strong alkaline irritant and the standing time (the time for standing after mixing the strong alkaline irritant and the fly ash) in various ways, and the amount of Si eluted from each of the obtained strong alkaline irritant pre-treated fly ash was measured.

[0047] (Strong alkaline stimulant selection experiment) -Types of strong alkaline irritants: potassium hydroxide, sodium hydroxide, aluminum hydroxide Addition rate and mixing conditions: 0.9% by mass (active ingredient relative to fly ash) of each strong alkaline irritant was added to the same lot of fly ash, mixed in a rotary mixer for 3 minutes, and then left to stand for 0, 5, and 10 minutes to obtain each powder sample. Measurement of the amount of eluted silicon: 5 g of the powder sample obtained above was mixed with 49.5 g of an aqueous NaOH solution, and stirred at 30°C for 3 hours. The mixture was then filtered, and the filtrate obtained was diluted 10 times with pure water to form a measurement solution. The amount of eluted silicon (ppm) was measured using an inductively coupled plasma (ICP) emission spectrometer.

[0048] The measured amounts of silicon eluted (ppm) are shown in Table 1 below when the type of strong alkaline irritant was varied, and in Table 2 below when the standing time was varied.

[0049] [Table 1]

[0050] The results in Table 1 show that the amount of silicon eluted from fly ash increases with any strong alkaline irritant, and that the amount of silicon eluted is greatest when potassium hydroxide is used.

[0051] [Table 2]

[0052] The results in Table 2 show that the amount of eluted silicon hardly increases when the mixture is left to stand for 0 minutes after mixing, and that the amount increases significantly when the mixture is left to stand for 5 minutes or more.

[0053] <Production of hardened body with high content of crystalline tobermorite> [Examples 1 to 8 and Comparative Examples 1 to 5] In order to confirm the effect of the manufacturing method of the hardened body with a high content of crystalline tobermorite according to the present invention, a test specimen of a hydraulic hardened body with a high content of crystalline tobermorite was actually manufactured. This test specimen was manufactured specifically as follows. That is, first, the materials shown in Tables 3 and 4 were mixed and kneaded to obtain a kneaded material. At this time, potassium hydroxide was used as the strong alkaline irritant type, and the strong alkaline irritant pre-treated fly ash was used by adding potassium hydroxide to the fly ash so that the amount shown in the potassium hydroxide addition rate (relative to the strong alkaline irritant pre-treated fly ash) in Tables 3 and 4 (0.01 mass% or more and 1.90 mass% or less) was shown in Tables 3 and 4 with respect to 100 mass% of the strong alkaline irritant pre-treated fly ash.

[0054] The mixed material was subjected to vacuum degassing extrusion molding to obtain a molded body.

[0055] (Evaluation of moldability of kneaded materials) To evaluate the moldability of the kneaded material, the material hardness of the molded body was measured using a needle penetration hardness tester from the start of kneading the kneaded material up to 2 hours. The evaluation criteria are as follows.

[0056] (Evaluation criteria for moldability evaluation) ○: Needle penetration hardness is less than 12 even after 2 hours or more. △: Needle penetration hardness exceeds 12 for more than 1 hour but less than 2 hours ×: Needle penetration hardness exceeds 12 within 1 hour

[0057] As a result of the moldability evaluation, it was found that the moldability decreased when potassium hydroxide was added in an amount of 1.90 mass% or more relative to 100 mass% of the fly ash pretreated with a strong alkaline irritant.

[0058] Molded bodies that were evaluated as ○ or △ in formability were subjected to primary curing at 65°C under normal pressure for 11 hours, and then autoclave curing at 170°C for 5 hours to obtain hardened bodies.

[0059] The obtained cured body was subjected to powder X-ray diffraction analysis to confirm the amount of crystalline tobermorite produced. The amount of crystalline tobermorite produced (relative value obtained from the powder X-ray diffraction analysis result) is shown in Tables 3 and 4 below.

[0060] [Table 3]

[0061] In the results in Table 3, when compared with Comparative Example 2, which has a high fly ash replacement rate of 85 mass%, it can be seen that in Examples 1 to 6, the amount of crystalline tobermorite produced is greater by using fly ash pre-treated with potassium hydroxide, and that in Examples 2 to 5, the amount of crystalline tobermorite produced is further increased by setting the potassium hydroxide in the range of 0.05 mass% or more and 1.40 mass% or less.

[0062] [Table 4]

[0063] In the results of Table 4, "silica powder content" is the content (mass%) of silica powder relative to 100% by mass of siliceous raw material, and "replacement rate of strong alkaline stimulant pre-treated fly ash" is the replacement rate (mass%) of strong alkaline stimulant pre-treated fly ash relative to 100% by mass of siliceous raw material. From Comparative Examples 1 to 4, when a part of the silica powder, which is a crystalline silica raw material, is replaced with fly ash not treated with a strong alkaline stimulant, increasing the replacement rate reduces the amount of crystalline tobermorite produced, but from Examples 4, 7, and 8, it can be seen that increasing the replacement rate of the strong alkaline stimulant pre-treated fly ash in the siliceous raw material increases the amount of crystalline tobermorite produced. However, as can be seen from Comparative Example 5, when the ratio of silica powder is less than 0.5% by mass relative to 100% by mass of siliceous raw material and the ratio of strong alkaline stimulant pre-treated fly ash is 50% by mass or more relative to 100% by mass of siliceous raw material, the amount of crystalline tobermorite produced decreases. Therefore, when the siliceous raw material contains fly ash that has not been treated with a strong alkali, it is preferable that the proportion of crystalline silica raw material such as silica powder is 3 mass% or more relative to 100 mass% of the siliceous raw material, and that the proportion of fly ash pretreated with a strong alkali irritant is less than 50 mass% relative to 100 mass% of the siliceous raw material.

Claims

1. A method for producing a crystalline tobermorite-containing hardened body, comprising autoclave curing a kneaded material containing cement and a siliceous raw material including fly ash premixed with a strong alkaline stimulant.

2. In claim 1, A method for producing a crystalline tobermorite-containing hardened body, wherein the ratio of the strong alkaline irritant is 0.05 mass% or more and 1.40 mass% or less relative to 100 mass% of fly ash pre-mixed with the strong alkaline irritant.

3. In claim 1 or 2, A method for producing a crystalline tobermorite-containing hardened body, in which the proportion of fly ash pre-mixed with the strong alkaline irritant is 99 mass% or less relative to 100 mass% of the siliceous raw material.

4. In claim 1 or 2, The siliceous raw material includes a crystalline silica raw material, fly ash pre-mixed with the strong alkaline stimulant, and fly ash not mixed with the strong alkaline stimulant; The ratio of the crystalline silica raw material is 3% by mass or more relative to 100% by mass of the siliceous raw material; A method for producing a crystalline tobermorite-containing hardened body, in which the proportion of fly ash pre-mixed with the strong alkaline irritant is less than 50 mass% relative to 100 mass% of the siliceous raw material.

5. In claim 1 or 2, A method for producing a crystalline tobermorite-containing hardened body, wherein the strong alkaline irritant contains potassium hydroxide, and the proportion of potassium hydroxide in the strong alkaline irritant is 90 mass% or more.

Citation Information

Patent Citations

  • Method for producing inorganic board

    JP2018126957A